A sustentabilidade e a economia de comunhão: um olhar sobre as práticas sustentáveis - Ferreira, Paulo André (2014)
This paper researched the meaning of sustainability for businesses in the Economy of Communion from the viewpoint of market practices on the model of Kjellberg and Helgesson (2007). Furthermore, an analysis of the possible influences of the National Association for an Economy of Communion on market practices of selected companies was conducted. The methodology used was a multiple case study, thus configuring a qualitative approach supported by interviews, electronic questionnaires, research content in the websites of the selected companies, the National Association for an Economy of Communion Economy of Communion and Electronics Magazine economy of Communion. Were also used as data collection photos copyrighted (the only company that was possible to carry out these pictures), and content analysis of a document received from one of the companies studied. For the primary objective was reached, visits were made to two companies, in order to interview the owners of these. In addition to personal interviews, an electronic questionnaire answered by two employees of the companies was conducted. To diagnose the possible influences of the said Association on market practices of companies, was prepared an electronic questionnaire completed by a representative of the Association, and we performed a content analysis of the electronic website of this organization. Regarding the possible influence of this Association on market practices of member companies, it was not possible to diagnose a practice that had a direct influence on market practices of companies in the Economy of Communion. However, from the identification of representative practice involving the construction of a shared meaning about the Economy of Communion, there is a possibility that this unproven practice manages some influence on market practices of the companies discussed scenario. The paper concludes by identifying some practices common to both companies market, signaling a new sustainable path, although there are limitations to overcome.